Thyroid follicular carcinoma presenting as metastatic skin nodules - Asad Jehangir; Ranjan Pathak; Madan Aryal; Anam Qureshi; Qasim Jehangir; Richard Alweis; Raymond Truex; William Kimmel (Greater Baltimore Medical Center, 2015)
Background: Follicular thyroid cancer (FTC) metastasizes most commonly to the lungs and non-cranial bones. Skull and skin are uncommon sites and usually manifest well after the diagnosis of primary malignancy. Metastasis to skull and skin as the presenting feature of FTC is infrequently reported in the literature. Case presentation: A 65-year-old Caucasian woman with a history of thyroid nodule presented with the complaint of rapidly growing skull nodules which had been present for 3 years but were stable previously. She denied any fevers, chills, history of trauma, or weight loss. She denied any history of smoking or head and neck irradiation. On physical examination, she had two non-tender gray cystic lesions - one on her left temporal region and the other on the right parietal region. Biopsy was consistent with metastatic FTC. Magnetic resonance imaging of the brain demonstrated 7.1×3.8 cm and 3.7×4.5 cm fairly homogeneous, enhancing, relatively well-defined masses centered in the posterior and left anterior lateral calvarium with intracranial and extracranial extensions but without any vasogenic edema or mass effect on the brain. Thyroid ultrasound showed numerous nodules in both lobes. The patient underwent a total thyroidectomy. Histopathological studies of the thyroid gland revealed a well-differentiated FTC in the left lobe. Then she underwent resection of the tumor in multiple stages. She did not have any recurrence of the FTC or metastases during the follow-up period and will be receiving radioactive iodine treatment. Conclusion: Bone and lung are the common sites of metastasis from FTC, but involvement of skull or skin is unusual, particularly as the presenting feature. Metastases from FTC should be in the differential of patients with new osteolytic hypervascular skull lesions or cutaneous lesions in head and neck area.